RICE, IT’S SUSTAINABLE PRODUCTION & MANAGEMENT, KEY TO FOOD SECURITY - Parnerkar, Laxmikant (Digital Repository of Theses - SSBM Geneva, 2022)
Food is the basic requirement for all living organisms to live life. Access to sufficient amounts of safe and nutritious food is key to sustaining life and promoting good health. We receive energy from food for varied activities, growth, and all bodily functions such as breathing, digesting meals, and staying warm. But one can observe that there are millions of people who do not possess the basic right to have food. Their inability to buy food has given rise to many problems. Malnutrition, problems relating to physical and mental health. In the year 2020, almost 811 million people worldwide went to bed hungry every night (World Health Organization Report, 2021). The horrifying statistics showcase the figure which increased to 957 million people in 2021 (UN Food Summit Report 2021). The research focuses on finding the solution to end the hunger crisis. The arena of research will revolve around how feeding people rice three times a day can reduce hunger problems and hunger-related stress for individuals and whether feeding people rice three times a day can be proved cost-effective and feasible to be scaled up to a larger scale? One grain, Rice is the sustainable solution for satisfying the hunger is the hypothecation of my research and study. The study will showcase all the aspects concerning the hypothesis. Rice can be consumed as a staple, and additionally, it will be cost-effective. My study and research postulate that based on the availability of the data given by the government and the recognized institutes, the hunger crisis can be cured if rice will be provided as a complete and sustainable meal. The need to consume food can only be stated and understood by those who go to bed hungry. Rice can prove a beneficial effort in reducing the hunger crisis. 9 | P a g e As rightly said “One cannot think well, love well, sleep well if one has not dined well.” -Virginia Wolf. (From her book- Room of One’s Own).